Growth and Characterization of M-Plane GaN Thin Films Grown on γ-LiAlO2 (100) Substrates. (18th October 2017) - Lin, Yu-Chiao; Lo, Ikai; Shih, Hui-Chun; Chou, Mitch M. C.; Schaadt, D. M.
Abstract : M -plane GaN thin films were grown on LiAlO2 substrates under different N/Ga flux ratios by plasma-assisted molecular beam epitaxy. An anisotropic growth ofM -plane GaN was demonstrated against the N/Ga flux ratio. As the N/Ga flux ratio decreased by increasing Ga flux, the GaN surface trended to a flat morphology with stripes along[ 112 - 0] . According to high-resolution X-ray diffraction analysis, Li5 GaO4 was observed on the interface between GaN and LiAlO2 substrate. The formation of Li5 GaO4 would influence the surface morphology and crystal quality.